GASTROPOD SHELLS USED BY Dardanus insignis (Decapoda, Anomura) NEAR ISLANDS IN THE UBATUBA REGION, SAO PAULO, BRAZIL - Frameschi, Israel Fernandes [UNESP]; Paula, Bruna Campos; Fernandes-Goes, Lissandra Correa; Rocha Duarte Alencar, Carlos Eduardo; Fransozo, Adilson [UNESP]; Morais Freire, Fulvio Aurelio de (Univ Federal Uberlandia, 2014)
The use of gastropod shells by hermit crabs is determined by the availability of shells in the environment or through selection for size and volume. This study analyzed patterns in the use of shells by Dardanus insignis (Saussure, 1858). From January 1998 to December 1999, 386 individuals were collected from two islands at Ubatuba, Sao Paulo. The crabs were measured for cephalothoracic shield length (CSL) and wet weight (CWW). The gastropod shells occupied by hermit crabs were identified, and the shell aperture width (SAW), dry weight (SDW) and internal volume (STY) were measured. The relationships between the dimensions of the gastropod shell and the hermit crabs were evaluated by linear regression analysis. Among the 11 species of gastropod shells used by D. insignis, the most often used was Olivancillaria urceus (31%), followed by Strombus pugilis (22%) and Siratus tenuivaricosus (18%). The shell of O. urceus was used most probably due to its high availability on Couves and Mar Virado islands. The most significant biometric parameter was shell aperture width (F=18.231; p<0.0001), highlighting the importance of this variable for the shell choice by D. insignis at both sites.
Keywords: Mollusca; Hermit crab; Habitat selection; Interspecific relationship; Morphometrics